Optimization of Drillstring Design to Produce More Stable Dynamic Drilling on Horizontal Drilling by Applying Different Stiffness Combinations - Dundie Prasetyo; Ratnayu Sitaresmi; Suryo Prakoso (Journal of Earth Energy Science, Engineering, and Technology, 2019)
Horizontal drilling technique is one of the methodologies that have been widely implemented recently to improve the production of oil and gas wells. Several directional drilling technologies can be utilized to drill the horizontal wells, vary from the simple mud motor technology to Bottom Hole Assembly (BHA) with the advanced motorized rotary steerable system. The most common challenges that are faced on horizontal drilling process are on the torque and the stick-slip throughout drilling process, which can be a technical limiter for the length of horizontal section that would be achieved. Stick-slip is the vibration that occurs due to cyclical rotation acceleration and deceleration of the bit, BHA or drill string. This speed fluctuation can be zero to rate of penetration (ROP) or far in excess of twice the rotational speed measured at the surface. Stick-slip can significantly decrease the ROP, increases tool failures and damage, affects borehole quality, and impacts the data acquisition. Several studies had been done on the stick-slip prevention and mitigation throughout creation of new technology and drilling parameters envelope throughout drilling operation, however no study has ever been done on the modification of the design and arrangement of the BHA itself to produce more stable BHA. Drill pipe is the longest component of the drill string and hence it has biggest contribution towards the drill string dynamic. This study will focus on the analysis of the combination of several designs of the drill-pipe and heavy weight drill-pipe (HWDP) that has different stiffness and characteristic to produce less vibration, more efficient drilling operation and to create zero impact on the data acquisition measured while drilling. FEA drilling dynamic simulator was used to optimize the drill sting configuration. The calculation is made from the depth of 750 m to 2801 m. Based on the drilling simulation results of FEA modeling, it is concluded that the minimum stiffness ratio to give stability of the drill string of Well-Z7 BHA and Well-Z6 BHA is 0.012175272 and 0.07366999, respectively.